La Poésie en classe du FLE au secondaire algérien : lire pour mieux écrire (Cas des élèves de 1ère année secondaire) (مجلة الواحات للبحوث والدراسات, 2021)
Learning a foreign language in Algeria, especially the French language, is a real challenge for secondary school students. We wanted to test the hypothesis that poetry contributes to the learning of FLE. Various research has been carried out around the literary text, especially poetry to prove the effectiveness of the latter in the act of learning the FLE. In the field of foreign language didactics, poetry has always been an enriching factor, given the peculiarity of the poetic text (rhymes, intonation, rhythm, vocabulary, structures ...). In this article, we try to show other ways of using the poem in order to enhance the learning of reading / writingKeywords:foreign language -  poetic - reading - writing- poem - learning – Motivation